Carbon outwelling and emissions from two contrasting mangrove creeks during the monsoon storm season in Palau, Micronesia. (5th March 2019) - Call, Mitchell; Sanders, Christian J.; Macklin, Paul A.; Santos, Isaac R.; Maher, Damien T.
Abstract: Mangroves sequester large amounts of carbon in soils but limited information is available on carbon losses from tropical mangrove systems. Here we quantify carbon outwelling, CO2 emissions and pore-water exchange rates from two nearby (∼2 km apart) tropical mangrove creeks located in different geomorphic settings on the island of Palau, Micronesia during the monsoon storm season. On average, POC and p CO2 were >100% higher and DOC, DIC and TA were 62%, 25%, 16% higher, respectively, from Creek 1 (located within a semi-enclosed bay) than from Creek 2 (located along the coast adjacent to fringing reefs). Both creeks were net exporters of DIC, DOC, POC, TA and emitters of CO2 . However, outwelling rates of POC, DIC and DOC and CO2 emissions were 27-fold, 8-fold, 4-fold and 3-fold higher at Creek 1. DIC outwelling (37%) and CO2 emissions (39%) were the major terms contributing to total carbon losses at Creek 1, whilst CO2 emission (61%) was the major contributor at Creek 2. Monsoon storms appeared to explain the organic carbon dynamics whilst tidal pumping appears to drive the inorganic carbon dynamics at both creeks. Our data demonstrates the considerable heterogeneity of mangroves creeks that are in close proximity and subject to similar weather conditions but in differing geomorphological settings.